"Walking with God": developing and pilot testing a manualised four-week program combining Christian meditation and light-to-moderate physical activity for daily stress. Issue 9 (20th October 2020) - Knabb, Joshua; Pate, Robert; Sullivan, Sean; Salley, Erik; Miller, Amy; Boyer, William
ABSTRACT: In the current study, the authors developed and pilot tested a manualized four-week program for Christian adults with daily stress, combining Christian meditation with light-to-moderate physical activity among a community sample of churchgoers ( N = 8). Although Eastern-influenced mindful walking and yoga practices are quite popular in the contemporary psychology literature as interventions for a wide variety of psychological problems, we wanted to offer a Christian-sensitive alternative for Christian adults to draw from their own faith tradition to impact psychological change. Over a four-week period of time, Christian participants were instructed to meditate on a short passage in Scripture as they engaged in a daily 30-minute movement and walking activity. On all four outcome variables, pilot results revealed that 75% of participants reported score changes in the hypothesized direction. To conclude, study limitations are reviewed, as are directions for future research.